1997
DOI: 10.1161/01.cir.96.1.19
|View full text |Cite
|
Sign up to set email alerts
|

Morning Hypercoagulability and Hypofibrinolysis

Abstract: Our data suggest that the diurnal changes in the plasma levels of activators and inhibitors of coagulation and fibrinolysis lead to corresponding changes in the activity state of these systems, leading to morning hypercoagulability and hypofibrinolysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
58
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(62 citation statements)
references
References 23 publications
4
58
0
Order By: Relevance
“…Prior investigators have demonstrated a surge in sympathetic activity accompanied by vagal withdrawal in the morning hours, leading to an increase in sheer forces secondary to elevation in blood pressure, heart rate, and the rate of pressure change (dP/dt). 22 Similarly, the equilibrium between thrombotic and thrombolytic factors changes in the early morning hours, leading to an increase in hypercoagulability (increased platelet aggregability and greater fibrinogen levels and factor VII activity) 23,24 and hypofibrinolysis (lower fibrinolytic activity). 24 This increases the viscosity of the blood, 25 which may, in turn, further contribute to the increased arterial sheer forces in the morning caused by a heightened sympathetic tone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior investigators have demonstrated a surge in sympathetic activity accompanied by vagal withdrawal in the morning hours, leading to an increase in sheer forces secondary to elevation in blood pressure, heart rate, and the rate of pressure change (dP/dt). 22 Similarly, the equilibrium between thrombotic and thrombolytic factors changes in the early morning hours, leading to an increase in hypercoagulability (increased platelet aggregability and greater fibrinogen levels and factor VII activity) 23,24 and hypofibrinolysis (lower fibrinolytic activity). 24 This increases the viscosity of the blood, 25 which may, in turn, further contribute to the increased arterial sheer forces in the morning caused by a heightened sympathetic tone.…”
Section: Discussionmentioning
confidence: 99%
“…22 Similarly, the equilibrium between thrombotic and thrombolytic factors changes in the early morning hours, leading to an increase in hypercoagulability (increased platelet aggregability and greater fibrinogen levels and factor VII activity) 23,24 and hypofibrinolysis (lower fibrinolytic activity). 24 This increases the viscosity of the blood, 25 which may, in turn, further contribute to the increased arterial sheer forces in the morning caused by a heightened sympathetic tone. Such forces presumably act on the aortic wall, which is inherently weakened by genetic and acquired disorders, causing triggering of AAD during the early morning hours.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10] Most studies of platelet function, coagulation, and fibrinolysis in patients with ischemic heart disease have focused on acute coronary syndromes. 1,2,[11][12][13][14][15] However, no study has examined angiographic findings and hematologic parameters to determine which characteristics place patients with stable ischemic heart disease at risk of transition to acute coronary syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…4 Fluctuations in coagulation factor levels able to influence the hemostatic balance might contribute to these adverse outcomes. Diurnal rhythms in levels of factor VII (FVII), 5 FVIII, 6 proteins C and S 7 , antithrombin, 7 and plasminogen activator inhibitor (PAI)-1 8 have been described in healthy humans. Temporal oscillations in prothrombin fragment F 1ϩ2 [5][6] and D-dimer, 6 markers of thrombin generation and fibrinolysis, have been also described.…”
mentioning
confidence: 99%